Nutritional Analysis of Different Maize Varieties and Silage Produced at Haor Area in Sylhet - Mahbub Hasan; Mohammed Mehedi Hasan Khan; Abdullah Al Mamun; Jannati Ful (Biota, 2025)
Maize and silage play a critical role in livestock nutrition, offering a cost-effective feed with a balanced nutrient profile. Improving maize and silage quality is essential for maximizing animal performance. This study aimed to evaluate the nutritional composition, fiber content, pH levels, and bacterial activity in silage made from two maize varieties—KMHB410 and HMS-PS-3355—using varying levels of molasses as an additive to improve silage quality. The study was conducted in Sylhet, Bangladesh where an absence of green grass causes the cattle to suffer from malnutrition throughout the lean season. Here silage was produced by mixing the chopped maize with 5% and 10% molasses, along with a control group. After 15 days of fermentation, the silage was assessed for dry matter (DM), ether extract (EE), crude protein (CP), crude fiber (CF), and acid detergent fiber (ADF), and the presence of Lactobacillus spp.  The study of Dry matter (DM) content ranged from (8.54 to 17.25) %, with HMS-PS-3355 at 17.25% and KMHB 10% molasses at 8.54% (P=0.002). Crude protein (CP) varied significantly (P=0.002), with KMHB C showing the highest value at 19.04%, while HMSC recorded 10.36%. The addition of molasses significantly reduced acid detergent fiber (ADF) content. Bacterial colony-forming units (CFU) were highest in the control silage (97×10⁶ CFU), while the 10% molasses treatment had the lowest count (38×10⁶ CFU), indicating that increased molasses concentrations reduced microbial growth. Confirmation and screening of Lactobacillus spp. in silage was carried out by culturing the microorganisms in a lactobacillus selective MRS media followed by different biochemical tests.